El renacer de los Reyes : imagen, contexto y significado del friso de Balamkú, Campeche, México - Salazar Lama, Daniel (Paris monographs in American archaeology, 2022)
The frieze of Structure 1-A Sub of Balamk,͠ Campeche, is one of the most complex Maya artistic expressions of the Classic period (250-900 AD). This study places the frieze within its historical framework so the monument may be better understood and the significance of its message revealed.